PENGARUH DOSIS PUPUK N DAN PUPUK KANDANG AYAM TERHADAP HASIL TANAMAN KUBIS (Brassica oleracea, L) VAR. GRAND 11 - Achmad Nurrudin; Gembong Haryono; Yulia Eko Susilowati (JURNAL VIGOR, 2020)
The research to study the effect of N fertilizer and chicken manure dose on the yield of cabbage (Brassica oleracea, L.) varieties Grand 11. Had been carried out from 10th June until 11th September 2018. The location is at Tejosari Village, Ngablak District, Magelang Regency on the altitude 1480 m above sea level high, type of the soil latosol with 6,8 of pH. The method of experiment is factorial (3x4) in randomized completely block design with three blocks. The treatment is the dose of N fertilizer consists of 50, 100, 150 kg / ha and the dose of chicken manure which consists of 5, 10, 15, 20 tons / ha. The results of the research shows that aplication of N fertilizer at a dose of 150 kg / ha given the highest yield in diameter of crop, height of crop, fresh weight of crop per plant, fresh weight of crop per m2, fresh weight of straw per plant and fresh weight of straw per m2. Aplication of chicken manure at a dose of 14.3 tons / ha given a diameter of crop 15.3 cm, a dose of 13.8 tons / ha given a height of crop 13.3 cm, a dose of 14.6 tons / ha given a fresh weight of crop per plant 1, 55 kg, a dose of 15.9 tons / ha given a fresh weight of crop per m213.6 kg, a dose of 17.3 tons / ha given a fresh weight of straw per plant 0.83 kg, and a dose of 14.6 tons / ha given a fresh weight of straw per m2 7.8 kg. N fertilizer and chicken manure given the same results on all parameters.